The effects of higher bioethanol blends on greenhouse gas emissions from the UK passenger car fleet at various time horizons during the transition to net zero: A review - Marchant, Denis; Christensen, Jesper; Davies, Huw (Universitas Muhammadiyah Surakarta, 2023)
There is a need to minimise the Greenhouse Gas Emissions (GHG) of petrol-powered cars during the transition to net zero. This research examines the effects on GHG from the recent adoption of E10 as the standard 95-octane petrol grade in the United Kingdom (UK). Also, it considers the potential of using higher bioethanol blends within the national car fleet and the effect of increased lifetime mileage due to the growing incidence of extended vehicle ownership. A comprehensive fleet turnover model and a separate numerical model to predict the GHG emissions for various powertrain types using different bioethanol blends were developed. Sensitivity studies that model the effects of different annual mileage using E10 and applying the proposed UK fleet composition scenarios at 10-year intervals from 2020 to 2050 were conducted. The results support the claimed percentage reduction of GHG emissions arising from the UK petrol car fleet using E10 when compared to E5 and establish that using a higher bioethanol blend such as E15 would provide still further reductions in most instances except in the case of plug-in hybrid vehicles where an increase in GHG emissions was observed at the 2030 and 2040 time horizons. An increase in annual mileage creates a linear increase in GHG emissions, although the rate of increase is not the same for each propulsion type. Such an increase can potentially disrupt the achievement of the UK's 2050 net zero target and future periodic carbon budgets.